2021
DOI: 10.1039/d1bm00703c
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of heparin using low-frequency sonophoresis in combination with sponge spicules for venous thrombosis treatment

Abstract: This study reports the use of low-frequency sonophoresis (LFS) in combination with sponge Haliclona sp. spicules (SHS), referred to as cSoSp (combined Sonophoresis and Spicules), can enhance the transdermal drug...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Zhu et al used a new combined system of low-frequency sonophoresis with an ultrasonic transducer and motor for calcein delivery, showing that a change of ultrasonic motor with static pressure can effectively control noninvasive permeability by adjusting motor driving amplitude voltage and duty ratio [ 70 ]. A study performed by Zhai and team used low-frequency sonophoresis for transdermal delivery of heparin with sponge spicules for the treatment of venous thrombosis, which confirmed that utilization of this combined technique significantly increases the transdermal delivery and is helpful for transdermal delivery of other hydrophilic macromolecules [ 71 ].…”
Section: Pharmaceutical and Biomedical Applications Of Sonophoresismentioning
confidence: 88%
“…Zhu et al used a new combined system of low-frequency sonophoresis with an ultrasonic transducer and motor for calcein delivery, showing that a change of ultrasonic motor with static pressure can effectively control noninvasive permeability by adjusting motor driving amplitude voltage and duty ratio [ 70 ]. A study performed by Zhai and team used low-frequency sonophoresis for transdermal delivery of heparin with sponge spicules for the treatment of venous thrombosis, which confirmed that utilization of this combined technique significantly increases the transdermal delivery and is helpful for transdermal delivery of other hydrophilic macromolecules [ 71 ].…”
Section: Pharmaceutical and Biomedical Applications Of Sonophoresismentioning
confidence: 88%